Answer:
c = 27
Explanation:
Solve for c:
(2 c)/3 = 18
Hint: | Multiply both sides by a constant to simplify the equation.
Multiply both sides of (2 c)/3 = 18 by 3/2:
(3×2 c)/(2×3) = 3/2×18
Hint: | Express 3/2×2/3 as a single fraction.
3/2×2/3 = (3×2)/(2×3):
(3×2)/(2×3) c = 3/2×18
Hint: | Express 3/2×18 as a single fraction.
3/2×18 = (3×18)/2:
(3×2 c)/(2×3) = (3×18)/2
Hint: | Cancel common terms in the numerator and denominator of (3×2 c)/(2×3).
(3×2 c)/(2×3) = (2×3)/(2×3)×c = c:
c = (3×18)/2
Hint: | In (3×18)/2, divide 18 in the numerator by 2 in the denominator.
18/2 = (2×9)/2 = 9:
c = 3×9
Hint: | Multiply 3 and 9 together.
3×9 = 27:
Answer: c = 27